2023
DOI: 10.3390/jcm12031033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Bi-Portal Endoscopic Spine Surgery and Unilateral Laminotomy for Bilateral Decompression in Multilevel Lumbar Stenosis Patients

Abstract: The clinical and radiological results before and after surgery were compared and analyzed for patients with multilevel lumbar stenosis who underwent bi-portal endoscopic spine surgery (BESS) and microscopic unilateral laminotomy for bilateral decompression (ULBD). We retrospectively identified 47 and 49 patients who underwent BESS and microscopic ULBD, respectively, who were diagnosed with multi-level lumbar stenosis. Clinical outcomes were evaluated using the visual analog scale score for both back and leg pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Following a rigorous assessment, 37 studies met the inclusion criteria and were included in this meta-analysis. 9,10,14,16,21-53 The Preferred Reporting Items for Systematic reviews and Meta-Analysis flow diagram of the literature search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Following a rigorous assessment, 37 studies met the inclusion criteria and were included in this meta-analysis. 9,10,14,16,21-53 The Preferred Reporting Items for Systematic reviews and Meta-Analysis flow diagram of the literature search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The portal change technique is considered the most challenging technique if the surgeon is unable to use both hands freely; however, it can be employed in clinical practice in procedures such as a laminectomy without flavectomy or discectomy; it can also be used to perform two-level surgeries. Moreover, in biportal spine fusion surgery, most L5–S1 procedures require left-hand operation for discectomy and cage placement [ 15 ]. The tilting technique is commonly employed in full endoscopic spine surgery; it has demonstrated efficacy as a multilevel procedure (more than three-level surgery) [ 16 ], with the ability to use more varied instruments [ 17 ] than the full endoscopic technique.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 32 33 ] FE-PSLD with uniportal approach is less invasive than biportal unilateral laminotomy for bilateral decompression (ULBD), even though the use of biportal ULBD was rapidly progressed due to its greater familiarity. [ 34 35 36 37 ] FE-PSLD can be argued to be superior to conventional surgery with several considerations: (1) Minimal blood loss and damaged anatomical structure, leading to less spinal instability complication and the need of future spinal fusion; (2) Ability to decompress single to multiple levels of LSS concurrently with single skin incision using uniportal access; and (3) Ability to decompress central and lateral recess LSS and excised herniated disc concomitantly with stenoscope by translaminar approach. [ 34 38 39 ] The feasibility of PSLD as effective management to replaced conventional open surgery for lumbar stenosis was also proven by Lim et al ., study on LSS patients which shown a significant increase of spinal canal volume, less soft-tissue damage by MRI, less hospital stay, and pain improvement with a mean score of 4.…”
Section: Discussionmentioning
confidence: 99%